2013
DOI: 10.2196/resprot.2547
|View full text |Cite
|
Sign up to set email alerts
|

Designing eHealth that Matters via a Multidisciplinary Requirements Development Approach

Abstract: BackgroundRequirements development is a crucial part of eHealth design. It entails all the activities devoted to requirements identification, the communication of requirements to other developers, and their evaluation. Currently, a requirements development approach geared towards the specifics of the eHealth domain is lacking. This is likely to result in a mismatch between the developed technology and end user characteristics, physical surroundings, and the organizational context of use. It also makes it hard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
187
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(205 citation statements)
references
References 54 publications
(64 reference statements)
1
187
0
Order By: Relevance
“…Where human-centered design is mainly "artefact-centered" and focused on identifying product features that are desired by (potential) end-users, value-based design aims to create useworthy design that caters for a person's values in life (Cockton, 2005). Values have been defined as "ideals or interests a (future) end user aspires to or has" (Van Velsen, Wentzel, & Van Gemert-Pijnen, 2013). For example, a value for parents can be that their children can grow up safely, and their actions in life will be motivated by this value.…”
Section: Introductionmentioning
confidence: 99%
“…Where human-centered design is mainly "artefact-centered" and focused on identifying product features that are desired by (potential) end-users, value-based design aims to create useworthy design that caters for a person's values in life (Cockton, 2005). Values have been defined as "ideals or interests a (future) end user aspires to or has" (Van Velsen, Wentzel, & Van Gemert-Pijnen, 2013). For example, a value for parents can be that their children can grow up safely, and their actions in life will be motivated by this value.…”
Section: Introductionmentioning
confidence: 99%
“…Focus groups offer an opportunity to obtain insights regarding the experiences, observations, and opinions of group members [40]. As Prahalad and Ramaswamy [39] point out, to understand the individual experiences for cocreation, the problem analysis, inspired by action research, sense making [41], and previous research [42], should encompass a general discussion of the entire process, including individual tasks, information, and communication needs, as well as the problems experienced and bottlenecks.…”
Section: Value Co-creation Dialogs Methods Number 1: Process Analysis mentioning
confidence: 99%
“…Cross-border healthcare faces differences in healthcare systems and policies, subsequently differentiating the quality of care. A comparison between the Netherlands versus Nord-Rhein Westfalen showed that in 2010 the German region had 32-fold higher incidence of MRSA than the Netherlands [41]. This big difference was attributable to the Dutch Search-and-Destroy policy for MRSA whereas Germany did not have such a preventive screening policy [42].…”
Section: Textbox 1: Eursafety Health-netmentioning
confidence: 99%
See 1 more Smart Citation
“…This chapter will focus on office workers and their wish to combat a sedentary lifestyle. In accordance with the user-centered design philosophy (Van Velsen et al 2013) we will clarify the context of the work in the form of the following scenario.…”
Section: Introductionmentioning
confidence: 99%